The first 24-hour bilirubin level as a predictor of hyperbilirubinemia in healthy term newborns - Rina Triasih; Ekawaty L Haksari; Achmad Surjono (Indonesian Pediatric Society Publishing House, 2016)
Background Early discharging healthy term newborns results in a difficulty to recognize hyperbilirubinemia. Objective The aim of this study was to determine the value of the first 24-hour total and unbound bilirubin levels in predicting hyper- bilirubinemia in healthy term newborns. Methods The first 24-hour and the 5 th day total and unbound bilirubin levels were measured in 84 healthy term newborns. The total bilirubin level was measured spectrophotometrically, whereas unbound bilirubin level was determined by peroxidase-oxidation method. Hyperbilirubinemia was defined as serum total bilirubin of >12.9 mg/dL or serum unbound bilirubin of >0.5 mg/dL after 24 hours of life. Results A correlation between the first 24-hour and the 5 th day total bilirubin levels was found (r= 0.53) with a regression equa- tion: Y (total bilirubin on day 5) = 4.69 + 1.15X (total bilirubin in the first 24 hours). In unbound bilirubin (r=0.31), the regression equa- tion was Y (unbound bilirubin on day 5) = 0.13 + 0.95X (unbound bilirubin in the first 24-hours). The relative risk for developing hy- perbilirubinemia in newborns whose TB 1 was >4.5 mg/dL was 12 (95% CI 2.9;48.4), whereas newborns whose UB 1 was >0.09 mg/ dL was 9.5 (95% CI 1.2;77.4). Conclusion Total bilirubin level of >4.5 mg/dL in the first 24 hours can predict the development of hyperbilirubinemia in term new- borns in the first week of life. Newborns with such level of total bilirubin need a longer stay or should visit the hospital on day 5-7